2017
DOI: 10.1080/02673843.2017.1389759
|View full text |Cite
|
Sign up to set email alerts
|

How socioeconomic circumstances, school achievement and reserve capacity in adolescence predict adult education level: a three-generation study in Finland

Abstract: Family socioeconomic circumstances directly influence adult education level. Adolescent psychosocial resources and health-promoting behaviour collectively termed as 'reserve capacity' and school achievement may likely mediate the effect of family socioeconomic circumstances on adult education level. We tested these relationships using 1985-1995 survey data on 12-18-year-old Finns (N = 41,822) linked with three-generation registry data of Statistics Finland until 2009. Results of the multinomial logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…As shown in previous studies (Slominski et al 2011;Brekke 2015;Acacio-Claro et al 2018), school achievement has the largest effect on adult education. This is to be expected, as good grades obtained in high school strongly predicted enrolment in higher education (Brekke 2015).…”
Section: Summary and Interpretation Of Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…As shown in previous studies (Slominski et al 2011;Brekke 2015;Acacio-Claro et al 2018), school achievement has the largest effect on adult education. This is to be expected, as good grades obtained in high school strongly predicted enrolment in higher education (Brekke 2015).…”
Section: Summary and Interpretation Of Resultssupporting
confidence: 67%
“…In this study, reserve capacity covers three dimensions, namely: perceived health, health-promoting behaviour and social support; with each dimension shown to independently predict adult education (Acacio-Claro et al 2018). We also add another factor, school achievement, as several studies have shown this to be one of the strongest predictors of adult education (Slominski et al 2011;Brekke 2015;Acacio-Claro et al 2018). Further, we propose that the pathways occurring in adolescence might interact with each other to affect adult education ( Figure 1).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…13,14,16 Parental socioeconomic determinants of offspring growth and development are also typically established well before pregnancy, 17,18 with the transition from adolescence to young adulthood marking a pivotal shift from family to individual educational, financial and other trajectories of socioeconomic attainment and role transitions. 14,19,20 The links between parental preconception exposures and early life offspring development have raised a question about whether preventive intervention should encompass the years before conception. 21,22 There are a range of possible mechanisms whereby preconception parental characteristics may affect offspring early life and growth, including the persistence of parental health risks and socioeconomic characteristics into pregnancy and the postpartum period, 23 and direct preconception effects on parental reproductive biology or the gamete that may affect future offspring development.…”
Section: Introductionmentioning
confidence: 99%